Comprehensive Assessment of the Virulence Factors sub 3, sub 6 and mcpA in the Zoonotic Dermatophyte Trichophyton benhamiae Using FISH and qPCR - Christina-Marie Baumbach; Antje Rückner; Lena Partusch; Eric Engel; Wieland Schrödl; Jule Kristin Michler (Journal of Fungi, 2021)
Skin infections by keratinophilic fungi are commonly referred to as dermatophytosis and represent a major health burden worldwide. Although patient numbers are on the rise, data on virulence factors, their function and kinetics are scarce. We employed an ex vivo infection model based on guinea pig skin explants (GPSE) for the zoonotic dermatophyte Trichophyton (T.) benhamiae to investigate kinetics of the virulence factors subtilisin (sub) 3, sub 6, metallocarboxypeptidase A (mcpA) and isocitrate lyase (isol) at gene level for ten days. Fluorescence in situ hybridization (FISH) and quantitative polymerase chain reaction (qPCR) were used to detect and quantify the transcripts, respectively. Kingdom-spanning, species-specific and virulence factor-specific probes were successfully applied to isolated fungal elements showing inhomogeneous fluorescence signals along hyphae. Staining results for inoculated GPSE remained inconsistent despite thorough optimization. qPCR revealed a significant increase of sub 3- and mcpA-transcripts toward the end of culture, sub 6 and isol remained at a low level throughout the entire culture period. Sub 3 is tightly connected to the de novo formation of conidia during culture. Since sub 6 is considered an in vivo disease marker. However, the presented findings urgently call for further research on the role of certain virulence factors during infection and disease.